Assessment of real-time method to detect liver parasite burden under different experimental conditions in mice infected with Plasmodium yoelii sporozoites. (December 2015) - Siddiqui, Arif Jamal; Bhardwaj, Jyoti; Goyal, Manish; Prakash, Kirtika; Soni, Awakash; Tiwari, Vishvanath; Puri, Sunil K.
Abstract: Use of highly specific, sensitive and quantitative Real-Time PCR (qRT-PCR) based methods greatly facilitate the monitoring of experimental drug intervention and vaccination efficacy targeting liver stage malaria parasite. Here, in this study we have used qRT-PCR to detect the growing liver stage parasites following inoculation of Plasmodium yoelii sporozoite. Route of sporozoite administration and size of the sporozoite inoculums are two major determinants that affect the liver stage parasite load and therefore its detection and quantification. Thus, these factors need to be addressed to determine the accuracy of detection and quantification of Real-Time PCR method. Furthermore, applicability of quantitative RT-PCR system needs to be confirmed by analyzing the effect of different antimalarials on liver stage parasite burden. We have observed that parasite burden in mice infected via intravenous route was higher compared to that in subcutaneous, intradermal and intraperitoneal route infected mice. Moreover, this method detected liver stage parasite load with as low as 50 sporozoites. The inhibition studies with primaquine and atovaquone revealed inhibition of liver stage parasite and well correlated with patency and course of blood stage infection. This study characterized the simplicity, accuracy, and quantitative analysis of liver stage parasite development by real time PCR under different experimental conditions. Use of real time PCR method greatly improves the reproducibility and applicability to estimate the efficacy and potency of vaccine or drug candidates targeting liver stage parasite. Highlights: Characterization of Real Time PCR assay to detect Plasmodium yoelii liver stage load. Detection of liver stage load after sporozoite inoculation via different routes. Detection of liver stage load with minimum 50 sporozoites. Quantitative assessment of liver stage load following drug intervention.